First person - Sabrina Alam (The Company of Biologists, 2022)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Sabrina Alam is first author on ' Snrpb is required in murine neural crest cells for proper splicing of genes essential for craniofacial morphogenesis', published in DMM. Sabrina is a PhD student in the lab of Dr Loydie A. Jerome-Majewska at McGill University, Montreal, Canada, investigating the role of splicing in the complexity of craniofacial development.